2016
DOI: 10.1016/j.aller.2015.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric disorders and symptoms severity in preschool children with atopic eczema

Abstract: Psychiatric illnesses are frequent in preschool children with atopic eczema.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
36
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 24 publications
4
36
0
Order By: Relevance
“…Two of these studies found a link between food allergies and neuropsychiatric conditions such as depression, anxiety, and ADHD [34,38], while others looked at immune dysregulation [33], asthma medications [37], and atopic eczema [35]. Our study supports the hypothesis that, in children diagnosed with ADHD, there is a subset of children who also suffer from atopic disease.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Two of these studies found a link between food allergies and neuropsychiatric conditions such as depression, anxiety, and ADHD [34,38], while others looked at immune dysregulation [33], asthma medications [37], and atopic eczema [35]. Our study supports the hypothesis that, in children diagnosed with ADHD, there is a subset of children who also suffer from atopic disease.…”
Section: Discussionsupporting
confidence: 80%
“…A number of studies have suggested a link between allergies and ADHD [34][35][36][37][38]. Two of these studies found a link between food allergies and neuropsychiatric conditions such as depression, anxiety, and ADHD [34,38], while others looked at immune dysregulation [33], asthma medications [37], and atopic eczema [35].…”
Section: Discussionmentioning
confidence: 99%
“…Although the results have been inconsistent, most studies have pointed to a positive association between AD and ADHD. [1,9,18,25,26,31] In an early study published in 1993, McGee et al [18] reported no significant association between ADHD behavior and a history of allergic disorders and that a diagnosis of ADHD was also not related to a positive skin test or serum IgE levels. In addition, Shyru et al [20] showed that bronchial asthma and allergic rhinitis, but not AD, were the risk factors for ADHD.…”
Section: Discussionmentioning
confidence: 99%
“…[1] It is well known that patients with AD have a higher risk of developing other allergic diseases. [7,2224] The presence of a correlation between ADHD/ASD and AD is a strong possibility, [25] but not all investigators agree with this conclusion (Table 1). [1,9,15,1821,2533] Reviewing the latest reports, most of the studies find in favor of a positive association between AD and ADHD/ASD in children, but investigations targeting longitudinal associations are still not being carried out in sufficient numbers.…”
Section: Introductionmentioning
confidence: 99%
“…AD not only causes various physical issues but also leads to psychological problems; patients experience frequent skin damage and sleep disorder due to extreme pruritus [6] and show depression, anxiety, attention deficit, tiredness, irritable mood, and aggressive behavior [7]. Parents of children with AD must strictly manage AD in daily life, such as consistent skin moisturization, food preparation, and environmental management, as well as general childcare for each stage of the child's growth; therefore, in addition to the pain experienced by the child, the degree of parenting stress is relatively higher than with other diseases [8].…”
mentioning
confidence: 99%